Comparison of Vectra three‐dimensional stereophotogrammetry measurement and tape measurement in the evaluation of perioperative volume change of the lower abdomen in association with lymphatic microsurgery. Issue 1 (23rd November 2020) - Akita, Shinsuke; Tokumoto, Hideki; Yamaji, Yoshihisa; Ishigaki, Tatsuya; Ogata, Hideyuki; Tezuka, Takafumi; Kosaka, Kentaro; Kuriyama, Motone; Mitsukawa, Nobuyuki
Abstract: Background: Although microsurgical treatment for lower extremity lymphedema (LEL) can improve lower abdominal morphology, methods to evaluate the volume change of the lower abdomen have yet to be established. This study aimed to determine the accuracy and reproducibility of three‐dimensional stereophotogrammetry (3DSM) in measuring the volume change in the lower abdomen. Methods: The perioperative volume changes in the lower abdomen were estimated using tape measurement (TM) and 3DSM in 26 patients with LEL. Thirteen patients with suprapubic lymphedema underwent abdominoplasty simultaneously. Each of them underwent multiple lymphaticovenular anastomoses (LVAs), and five of them underwent vascularized lymph node transfer, simultaneously. Thirteen patients with pelvic lymphatic fluid underwent multiple LVAs. Two patients underwent this surgery twice. When assessed on the Internal Society of Lymphology scale, eight patients were Stage I, 10 patients were Stage II, four patients were late Stage II, and four patients were Stage III. The difference between the two measurement methods and reproducibility of each method were analyzed. Results: During a mean follow‐up period of 6 months, all patients had no postoperative complications and their chief complaint improved. The calculated reduction volume between TM and 3DSM showed a high correlation (p < .0001, r = .84). The reduction volume based on TM was significantly larger than 3DSM (991.1 ± 460.3 ml vs. 862.3 ± 333.5 ml, p = .02). The interrater ICC was 0.94 and 0.98 based on TM and 3DSM, respectively. Conclusion: 3DSM may be a useful method for assessment of the lower abdominal morphology due to its high accuracy and reproducibility.